Osteoblastic Responses to TGF-β during Bone Remodeling - Erlebacher, Adrian (The American Society for Cell Biology, 1998)
Bone remodeling depends on the spatial and temporal coupling of bone formation by osteoblasts and bone resorption by osteoclasts; however, the molecular basis of these inductive interactions is unknown. We have previously shown that osteoblastic overexpression of TGF-β2 in transgenic mice deregulates bone remodeling and leads to an age-dependent loss of bone mass that resembles high-turnover osteoporosis in humans. This phenotype implicates TGF-β2 as a physiological regulator of bone remodeling and raises the question of how this single secreted factor regulates the functions of osteoblasts and osteoclasts and coordinates their opposing activities in vivo. To gain insight into the physiological role of TGF-β in bone remodeling, we have now characterized the responses of osteoblasts to TGF-β in these transgenic mice. We took advantage of the ability of alendronate to specifically inhibit bone resorption, the lack of osteoclast activity in c-fos(−/−) mice, and a new transgenic mouse line that expresses a dominant-negative form of the type II TGF-β receptor in osteoblasts. Our results show that TGF-β directly increases the steady-state rate of osteoblastic differentiation from osteoprogenitor cell to terminally differentiated osteocyte and thereby increases the final density of osteocytes embedded within bone matrix. Mice overexpressing TGF-β2 also have increased rates of bone matrix formation; however, this activity does not result from a direct effect of TGF-β on osteoblasts, but is more likely a homeostatic response to the increase in bone resorption caused by TGF-β. Lastly, we find that osteoclastic activity contributes to the TGF-β–induced increase in osteoblast differentiation at sites of bone resorption. These results suggest that TGF-β is a physiological regulator of osteoblast differentiation and acts as a central component of the coupling of bone formation to resorption during bone remodeling.